Strategi Penanganan Paham Keagamaan Menyimpang dalam Perspektif Dakwah (Studi pada Kasus-Kasus yang Ditangani MUI NTB) - Faizah Faizah; Muhammad Thohri (Universitas Islam Negeri (UIN) Mataram, 2018)
Majelis Ulama Indonesia (MUI) merupakan wadah berkumpulnya para ulama yang memiliki kredibilitas dan kapasitas keilmuan untuk memberikan penilaian terhadap ajaran sesat. MUI berperan menangani persoalan keummatan yang bersifat multidimensi terutama persoalan faham keagamaan. Penelitian ini merupakan field research yang termasuk dalam katagori kualitatif dengan lokus MUI provinsi Nusa Tenggara Barat (NTB). Teknik pengumpulan data menggunkanan teknik wawancara, observasi dan dokumentasi. Setelah melakukan kajian, baik melalui studi lapangan maupun studi literatur, maka dapat diambil kesimpulan: (1) Faham sesat di NTB, muncul hampir setiap tahun baik aliran transnasional yang berciri sosio-politik maupun lokal berciri sosio-ekonomis yang muncul sebagai konstruksi personal-awam melalui proses kontemplasi batin, (2) Faham sesat transnasional maupun lokal ditangani responsif secara koordinatif-tentatif oleh beberapa komisi di MUI dan kerjasama dengan jajaran pemerintah daerah maupun MUI Pusat, dan (3) Dakwah struktural yang massif dan memaksimalkan seluruh unsur MUI dan mitra kerja MUI belum digarap dengan baik dengan multipendekatan, multi-kanal dan professional. Title: Handling Strategies of Deviant Religious Ideology in Da’wah Perspective (Study in Cases Handled by MUI NTB) Authors: Faizah, and Muhammad Thohri Abstract: Indonesian Council of Ulama (MUI) is a gathering place for scholars (ulama) who have scientific credibility and capacity to provide an assessment to the misguided doctrine. MUI has a role in handling the community issues which have multidimensional characteristics, especially the issue of religious ideology. This research was a field research which is included in the qualitative category with the locus of the MUI in the province of West Nusa Tenggara (NTB). To collect the data and information about handling strategies of deviant religious ideology and doctrine in da'wah perspective, the researcher used three data collection techniques in this research, namely: interview, observation and documentation techniques. After conducting the research, both field studies and literature studies, it can be concluded that: (1) misguided ideology in NTB appears almost every year both transnational ideology which has socio-political characteristics and local ideology which has socio-economic characteristics which emerge as a personal-common construction through a process of spiritual contemplation. Transnational and local misguided ideologies are handled responsively and coordinative-tentative by several commissions at the MUI and they collaborate with the regional government and the Central MUI. The massive structural da’wah and maximizing all elements of the MUI and working partners of the MUI have not been done well with multi-approaches, multi-channels and professionals.